Differentiated Instruction between Theories of: Multiple Intelligences and Learning Styles - Alnasser, Mohammed Abdullah (Journal of Educational and Psychological Sciences, 2020)
This present study aims to suggest visualization for Differentiated Instruction Based on Theoretical and Analytic Methodology. The researcher review two distinguished theories: Multiple Intelligences and Learning Styles, And Investigating the aspects of similarities and differences of these two theories, and reviewing studies which investigate the two theories together, then suggest visualization for Implementing Differentiated Instruction by Integrating Method Including these two theories.
Keywords: Differentiated Instruction; Multiple Intelligences; Learning Styles